ETIKA PROFESI DAN IMPLEMENTASINYA DI INDONESIA - Melita, Yerah (Jurnal Insani, 2018)
Ethics is a guide, reference or guide of man in attitude and behavior. Ethics are made not only known and understood, but also more importantly can be implemented in daily life in the community, both in the family and when carrying out duties and responsibilities and work in accordance with the profession that they do. Knowing and understanding professional ethics is not too difficult, but implementing it is not easy. It takes a strong moral awareness of the practitioners or the people who run the profession. This also applies to the profession of journalists in Indonesia who have a Journalistic Code of Ethics that has been mutually agreed among journalists.